1962
DOI: 10.1002/art.1780050503
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of variation in systemic and articular indexes

Abstract: Serial appraisals of rheumatoid activity by the systemic and articular indexes, performed by seasoned observers on patients who were accustomed to this type of examination, show an interobserver variation no greater than interlaboratory variations in determinations made on stock samples for uric acid, albumin and hemoglobin. However, the variation found when medical students examined new patients was considerably higher. Interobserver variation was not significantly greater than intraobserver variation. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1963
1963
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This difference is less than the usual coefficients of variation of the measures rheumatologists use to assess response. Thus, for example, the coefficient of variation for morning stiffness was >loo%, that for joint tenderness count was 27%, and that for a combined index was 13% (23). While CMT-N was statistically more effective than some of the other regimens, it is not significantly more effective clinically.…”
Section: Discussionmentioning
confidence: 92%
“…This difference is less than the usual coefficients of variation of the measures rheumatologists use to assess response. Thus, for example, the coefficient of variation for morning stiffness was >loo%, that for joint tenderness count was 27%, and that for a combined index was 13% (23). While CMT-N was statistically more effective than some of the other regimens, it is not significantly more effective clinically.…”
Section: Discussionmentioning
confidence: 92%
“…The National Institutes of Health Activity Record was developed to measure outcomes of an energy conservation program and was reported as having no standard scoring system and did not show sensitivity to change (30, 41). The time to onset of fatigue question showed that fatigue did not improve in an NSAID trial, but little information on construct or criterion validity could be found (42, 43).…”
Section: Resultsmentioning
confidence: 99%
“…The measures of rheumatoid disease which are clinically in use today include: an addition of the number of tender joints, a summation of the number of swollen joints, the time necessary to walk 50 feet, visual analog scales of disease activity and patient pain, grip strength, erythrocyte sedimentation rate (ESR), and questionnaires measuring the abil ity to carry on activities of daily living. (Lansbury, Baier and McCracken, 1962;Smythe and Buchanan, 1988). These measures vary spontaneously and are subject to major measurement error, ~ (see Table 1) (Furst, 1988).…”
Section: Interleukin-2 (Il-2) Is Produced By Activated T-cells and Ammentioning
confidence: 99%